Abundant unusual neural branches from the fornix in patients with mild traumatic brain injury: A diffusion tensor tractography study. (19th September 2017) - Jang, Sung Ho; Lee, Han Do
ABSTRACT: Objectives : Since the introduction of diffusion tensor tractography (DTT), several studies have been reported on the mechanisms for the recovery of an injured fornix in patients with traumatic brain injury (TBI). We report on patients who showed abundant unusual neural branches from the fornix following mild TBI using DTT. Methods : Five patients with mild TBI who complained of memory impairment and showed preserved integrity of the fornix with abundant unusual neural branches on DTT, and eight normal subjects were recruited. DTT parameters (fractional anisotropy [FA] and fibre number) of the fornix were measured. Results : All five patients showed memory impairment on only one subscale of the Memory Assessment Scale (MAS), although the global MAS was within the normal range. The FN of the fornix was increased by more than two standard deviations in all five patients compared with that of normal subjects, while the FA value was within two standard deviations of that of normal subjects. On the DTT for the fornix of the patients, three types of unusual neural tracts from the fornix not observed in normal subjects were observed in patients. Conclusion : The abundant unusual neural branches from the fornix might be a recovery phenomenon of a mildly injured fornix, although the integrity of the fornix was preserved in these patients.